Comparative Analysis of Charge Recombination Dynamics in Dye-Sensitized Solar Cells with different Counter Electrodes - Evi Nur Azizah; Nunik Nurhayati; Lalu Jihad Al Jazeera; Lia Yuliantini; Mohammad Hatta; Tahta Amrillah; Natalita Maulani Nursam; Yuliar Firdaus (National Research and Innovation Agency, 2025)
Counter electrodes are essential in dye-sensitized solar cells (DSSCs) for facilitating charge transfer and catalyzing the regeneration of the electrolyte, impacting overall efficiency. Common counter electrode materials include platinum (Pt), poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS), and graphene, each with distinct advantages and challenges. Pt, a traditional choice, offers excellent catalytic activity but is expensive and scarce. PEDOT:PSS, a conductive polymer, is cost-effective and easily deposited but often suffers from high recombination losses and lower efficiency. Graphene, known for its high conductivity and large surface area, is emerging as a promising alternative. However, a lack of comparative studies on how different counter electrode materials influence recombination dynamics limits the understanding needed for optimizing DSSC performance. This study addresses this gap by examining Pt, graphene, and PEDOT:PSS -based counter electrodes, analyzing their effects on charge transfer, recombination behaviour, and efficiency through J-V measurements, charge extraction, and transient photocurrent (TPC) as well as transient photovoltage (TPV) analyses. Graphene-based DSSCs show superior performance, achieving the highest photocurrent density and power conversion efficiency up to 5.12% at an intensity equivalent to 1 sun (100 mWcm-2), due to enhanced charge extraction and minimized recombination. TPC data reveal that graphene supports faster charge transport, while TPV analysis shows longer electron lifetimes than PEDOT:PSS-based DSSCs. In contrast, PEDOT:PSS-based DSSCs exhibit high recombination losses, lower photocurrent, and s-shaped J-V curves, indicating high resistance of limited charge transfer efficiency. These findings highlight graphene’s potential as an optimal counter electrode material for efficient, high-performance DSSCs.